NSRG-11. DIVERSION OF CSF WITH PROGRAMMABLE VENTRICULOPERITONEAL SHUNTS: ROLE WITH INTRAVENTRICULAR RADIOIMMUNOTHERAPY. Issue 2 (22nd June 2018) - Kramer, Kim; Donzelli, Maria; Grkovski, Milan; Greenfield, Jeffrey; Souweidane, Mark; Taskar, Neeta Pandit
Abstract: BACKGROUND: The success of programmable ventriculoperitoneal shunts (pVP-shunts) in fully diverting therapeutics into cerebrospinal fluid (CSF) has not been reported. METHODS: Patients with CNS tumors under consideration for intraventricular radioimmunotherapy were assessed with pre-treatment CSF flow studies. pVP-shunts were adjusted pre-administration, and readjusted to baseline approximately 4-5 hours post. 111-In-DTPA was injected into the pVP-shunts; nuclear images obtained immediately, 4-5 and 24 hours post-injection. Patients receiving radioimmunotherapy underwent the same procedure, with serial PET or SPECT imaging 2 to 48 hours using 124I/131I radiolabeled antibody. Imaging assessed CSF flow and adequacy of drug administration. RESULTS: 21 patients (ages 1 - 51 years) had medulloblastoma (N=9), choroid plexus carcinoma (N=2), rhabdoid tumor (N=2), ependymoma (N=1), metastatic neuroblastoma (N=4), retinoblastoma (N=2), or melanoma (N=1). On CSF flow studies, 5 patients (24%) had normal flow, 10 (48%) had delayed thecal sac ascent or descent. Of these, 4 had shunt revision or contralateral Ommaya placement; 3 then achieved normal flow. Six patients (29%) had adequate CSF flow down the thecal space with some activity in the peritoneum (6-23%). Similar drug localization was observed on nuclear scans after radioimmunotherapy, with PET and SPECT having greater sensitivity in detecting activity in the peritoneum. CONCLUSIONS: While pVP-shunts are effective intraventricular devices, normal CSF flow is seen in 24% of patients. Drug accumulation (up to 23%) in the peritoneum is still observed in 29% of patients. Shunt revision and/or contralateral Ommaya catheter placement may still be required to address drug delivery.